Angiotensin Receptor Antagonist-Neprilysin Inhibitor (ARNI) therapy as a new hope in the population of people with heart failure with reduced ejection fraction (HFrEF) - Przemysław Żelazny; Joanna Filipczak; Oliwer Sygacz; Sebastian Bróż; Sara Dankiewicz; Aleksandra Swora; Joanna Borowik; Wojciech Brodowski; Piotr Pawłowski; Katarzyna Basta-Arciszewska (Kazimierz Wielki University, 2022)
Introduction: Heart failure affects an estimated 23 million people, as many as 50% of whom suffer from a heart failure with reduced ejection fraction (HFrEF), in which the left ventricle ejection fraction is <40% and is accompanied by clinical symptoms. Given the high mortality rate in this group of patients and the continuous suboptimal control of the condition, novel pharmacotherapy regimens are needed to slow the progression of the disease. Preliminary studies report a positive effect of including an angiotensin receptor antagonist and neprilysin inhibitors (ARNIs) in this group of patients. Aim of the study: The aim of the study was to summarize the benefits of ARNI in a group of patients with HFrEF. Methods and materials: This article is based on the literature found in PubMed Database with use of keywords such as "ARNI", "neprilysin inhibition", HFrEF", "heart failure" Results: The benefits of ARNI therapy in patients with HFrEF originate from reversing myocardial remodeling and increasing left ventricular ejection fraction. ARNI therapy is associated with reduced number of hospitalizations and a lower need for intensive treatment. In addition, ARNI use reduces the risk of cardiovascular death and is responsible for lower overall mortality rate compared to pharmacotherapy with angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor antagonists (ARBs). Conclusion: ARNIs in patients with HFrEF have a positive effect on the rate of cardiovascular hospitalization, as well as reducing cardiovascular-related mortality and total mortality. Future research studies should evaluate the predictive factors of response to treatment with this group of drugs using larger groups of patients.